Multifunctional evolution of B and AGL6 MADS box genes in orchids - Hsing-Fun Hsu (Nature Portfolio, 2021)
B class AP3/PI and AGL6-like MADS proteins determine lips and sepals/petals identities in orchids. Here, the authors characterize the extended function of OAP3/OPI/OAGL6 in regulating the specific structure of the lateral sepals, pigmentation/senescence of the perianth and abscission of the pedicel.